Candidates undertaking (invigilated) assessment online show no differences in performance compared to those undertaking assessment offline. (3rd June 2021) - Hope, David; Davids, Veronica; Bollington, Lynne; Maxwell, Simon
Abstract: Background: Medical education has historically relied on high stakes knowledge tests sat in examination centres with invigilators monitoring academic malpractice. The COVID-19 pandemic has made such examination formats impossible, and medical educators have explored the use of online assessments as a potential replacement. This shift has in turn led to fears that the change in format or academic malpractice might lead to considerably higher attainment scores on online assessment with no underlying improvement in student competence. Method: Here, we present an analysis of 8092 sittings of the Prescribing Safety Assessment (PSA), an assessment designed to test the prescribing skills of final year medical students in the UK. In-person assessments for the PSA were cancelled partway through the academic year 2020, with 6048 sittings delivered in an offline, traditionally invigilated format, and then 2044 sittings delivered in an online, webcam invigilated format. Results: A comparison (able to detect very small effects) showed no attainment gap between online ( M = 0.762, SD = 0.34) and offline ( M = 0.761, SD = 0.34) performance. Conclusions: The finding suggests that the transition to online assessment does not affect student performance. The findings should increase confidence in the use of online testing in high-stakes assessment.